Imaging Tumor Response and Tumoral Heterogeneity in Non–Small Cell Lung Cancer Treated With Antiangiogenic Therapy: Comparison of the Prognostic Ability of RECIST 1.1, an Alternate Method (Crabb), and Image Heterogeneity Analysis. Issue 5 (September 2015) - Yip, Connie; Tacelli, Nunzia; Remy-Jardin, Martine; Scherpereel, Arnaud; Cortot, Alexis; Lafitte, Jean-Jacques; Wallyn, Frederic; Remy, Jacques; Bassett, Paul; Siddique, Musib; Cook, Gary J.R.; Landau, David B.; et al.
Abstract : Purpose: We aimed to assess computed tomography (CT) intratumoral heterogeneity changes, and compared the prognostic ability of the Response Evaluation Criteria in Solid Tumors (RECIST) 1.1, an alternate response method (Crabb), and CT heterogeneity in non–small cell lung cancer treated with chemotherapy with and without bevacizumab. Materials and Methods: Forty patients treated with chemotherapy (group C) or chemotherapy and bevacizumab (group BC) underwent contrast-enhanced CT at baseline and after 1, 3, and 6 cycles of chemotherapy. Radiologic response was assessed using RECIST 1.1 and an alternate method. CT heterogeneity analysis generating global and locoregional parameters depicting tumor image spatial intensity characteristics was performed. Heterogeneity parameters between the 2 groups were compared using the Mann-Whitney U test. Associations between heterogeneity parameters and radiologic response with overall survival were assessed using Cox regression. Results: Global and locoregional heterogeneity parameters changed with treatment, with increased tumor heterogeneity in group BC. Entropy [group C: median −0.2% (interquartile range −2.2, 1.7) vs. group BC: 0.7% (−0.7, 3.5), P= 0.10] and busyness [−27.7% (−62.2, −5.0) vs. −11.5% (−29.1, 92.4), P= 0.10] showed a greater reduction in group C, whereas uniformity [1.9% (−8.0, 9.8) vs. −5.0% (−13.9, 5.6), P= 0.10] showed a relative increase after 1 cycle but did not reach statistical significance. Two (9%) and 1 (6%) additional responders were identified using the alternate method compared with RECIST in group C and group BC, respectively. Heterogeneity parameters were not significant prognostic factors. Conclusions: The alternate response method described by Crabb identified more responders compared with RECIST. However, both criteria and baseline imaging heterogeneity parameters were not prognostic of survival. Abstract : Supplemental Digital Content is available in the text.